High-Efficient and Broadband Acoustic Insulation in a Ventilated Channel With Acoustic Metamaterials - Su, Zihao; Zhu, Yifan; Gao, Siyuan; Luo, Hao; Zhang, Hui (Frontiers in Mechanical Engineering, 2022)
Acoustic insulation in ventilated structures is an important problem in acoustic engineering with many potential practical applications, such as the noise control for ventilating ducts of buildings, vehicles, or air conditioners. Acoustic metamaterial is a good candidate for the design of acoustic insulation for ventilated channel (AIVC) because the structural design with hard boundary has longer lifetime than conventional sound-absorbing cotton. In this paper, an AIVC with an open region and narrow channels of different lengths is proposed. We numerically and experimentally demonstrate its acoustic insulation larger than 20 dB (T>0.99) within approximately 500-1200 Hz with a subwavelength channel length of λ/6. The parameter dependences and air flow effect are numerically studied. Our findings show an alternative design of AIVC that may have applications in noise control and architectural acoustics.